Morphological and Genetic Analysis of the Acerentomon doderoi Group (Protura: Acerentomidae) with Description of A. christiani sp. nov. - Julia Shrubovych; Daniela Bartel; Nikolaus Urban Szucsich; Monika Carol Resch; Günther Pass (PLoS ONE)
Acerentomon christiani sp. nov. is described from Vienna, Austria. The new species is a member of the "doderoi" group, characterized by the presence of seta x on tergite VII. It is most similar to A. gallicum, A. brevisetosum and A. tenuisetosum, but differs from these species in the length of foretarsal sensillum c and certain other chaetotaxic measurements and indices. In addition to the morphological description, the DNA barcoding region of the mitochondrial cytochrome c oxidase subunit 1 gene (COI) and the 28S ribosomal RNA of the new species are provided. The morphological characters and the barcode of the new species are discussed in comparison to those of other Acerentomon species. An identification key to all known Acerentomon spp. of the "doderoi" group is given.